2008
DOI: 10.1590/s1676-24442008000600008
|View full text |Cite
|
Sign up to set email alerts
|

Estudo retrospectivo dos casos diagnosticados como ameloblastoma no Serviço de Anatomia Patológica do Hospital Universitário Antônio Pedro entre 1997 e 2007

Abstract: Introdução: O ameloblastoma é um tumor odontogênico de origem epitelial que, pela freqüência, subtipos clínicos, grande capacidade infiltrativa e alta tendência à recorrência tem merecido bastante atenção. Objetivo: Realizar estudo retrospectivo dos casos diagnosticados histopatologicamente de ameloblastoma no Serviço de Anatomia Patológica do Hospital Universitário Antônio Pedro da Universidade Federal Fluminense (HUAP/UFF) no período de 1997 a 2007. Material e métodos: Foram selecionados casos de ameloblasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
5
4
0
1
Order By: Relevance
“…Our study has identified that the mandible was the most affected site, posterior region with 36 cases (90%), the anterior with 2 cases (5%), which is in agreement with almost studies [4,6,8,17].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study has identified that the mandible was the most affected site, posterior region with 36 cases (90%), the anterior with 2 cases (5%), which is in agreement with almost studies [4,6,8,17].…”
Section: Discussionsupporting
confidence: 93%
“…There is no predilection for sex [9]. In the present study gender distribution showed no preferences, as most reports in literature [1,[6][7][8]21].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This is in accordance with the literature, in which it is usually shown that there is no notable relation to gender regarding occurrences of ameloblastoma. 1 , 3 , 8 , 11 , 12 In a study conducted on 116 patients, the ratio between the male and female genders was 1.2:1, 5 and a single study in which this ratio was analyzed found that it was 2:1, with predominance among males. 13…”
Section: Discussionmentioning
confidence: 98%
“…This is also confirmed in the literature, where these tumors have been shown to be predominantly in adults, generally in their fourth or fifth decade of life. 3 , 12 …”
Section: Discussionmentioning
confidence: 99%